An integrated, multidisciplinary management team intervention to improve patient-centeredness, HIV, and maternal-child outcomes in Lesotho: formative research on participatory implementation strategies - Laura K. Beres; Mammatli Chabela; Matseliso Masitha; Zachary Catanzarite; Vincent J. Tukei; Lynne Mofenson; Appolinaire Tiam; Lauren Greenberg; Majoalane Mokone; Ramatlapeng Thabelo; Masepeli Nchephe; Tsietso Mots’oane; et al. (BMC Health Services Research)
Abstract Background Reducing perinatal HIV transmission and optimizing maternal and child health (MCH) outcomes in high HIV prevalence settings is an urgent, but complex, priority. Extant interventions over-emphasize individual-level provider and patient behaviors, and neglect critical health systems-level changes. The ‘Integrated Management Team to Improve Maternal-Child Outcomes (IMPROVE)’ study implemented a three-part, patient-centered, health-systems-level intervention to improve MCH and HIV outcomes in Lesotho. Ensuring intervention fit within the health systems context is important, but often overlooked. This manuscript describes implementation research conducted to tailor and adapt intervention implementation to optimize appropriateness, acceptability, and feasibility. It identifies resulting implementation variation across study sites and lessons learned. Methods The research team reviewed intervention implementation documentation and conducted structured reflections to: 1) assess implementation strategy adaptations, 2) identify facility-specific strategies employed to improve the MCH patient experience, and 3) synthesize lessons. Results Facility-based, integrated, multi-disciplinary management teams (MDT) were feasible and acceptable to establish through engagement with facility leadership and facilitation of a participatory training curriculum that established shared values between cadres supporting MCH, and identified facility-specific service delivery gaps and potential solutions. Ongoing MDT meetings provided coordination between facility and community-based MCH service providers to implement early ANC follow-up. Facility-specific improvement strategies included fee, staffing, and patient documentation-based changes. Piloting Positive Health, Dignity, and Prevention-focused counseling approaches resulted in tailored job aids pre-implementation. Leadership involvement was critical for improved coordination while staff turnover and competing donor priorities challenged MDT efforts. Conclusions IMPROVE created facility-specific adaptation opportunities through participatory intervention implementation practices. The MDTs, benefitting from leadership support, built relationships between HCW cadres, led facility-specific quality improvements, and, importantly, offered HCWs sought-after positive feedback by recognizing HCW efforts. The coordination, monitoring and cross-cadre communication functions of the MDTs supported implementation of other interventions, and may serve as a valuable platform for improving patient-centered care practices in similar settings and for other health services. Trial registration number: NCT04598958, 05 October 2020, retrospectively registered. Trial registration ClinicalTrials.gov, NCT04598958. Registered 05 October 2020—Retrospectively registered, https://clinicaltrials.gov/ct2/show/record/NCT04598958